Nexus of Inflation, Governance and Corruption Control of Nepal: A Quantile Autoregressive Distributed Lag Analysis - Gajurel, Ram Prasad; Rai, Arjun; Poudel, Tanka Mani (Curriculum Development Journal, 2023)
Corruption is a stigma of democracy. In Nepal, corruption is typically attributed to inflation and poor governance. This paper intends to examine the nexus of inflation and governance on corruption control, using the time series data from 1996 to 2021. The paper has employed the ordinary least squares (OLS) and quantile auto regressive distributed lag (QARDL) models where the QARDL model adeptly handles structural breaks and non-normal data, offering subtle insights into the diverse impacts of inflation and governance on corruption. The OLS results revealed that increases in inflation were beneficial in combating corruption, with regulatory quality and political stability indicators having a similar impact. The findings of QARDL revealed that inflation’s effect on corruption in the short run varies, shifting from exacerbation to mitigation across quantiles. Furthermore, the results indicated that the rule of law and political stability effectively combated corruption, while regulatory quality and voice and accountability yielded mixed results. The long-run QARDL result revealed that specific quantiles of inflation, political stability, and rule of law were effective in combating corruption, whereas higher-order quantiles of regulatory quality and voice and accountability could contribute to corruption, along with certain levels of employment, broad money supply, and GDP which improved corruption control in Nepal. Policymakers should prioritize moderate inflation, enhance governance, strengthen regulations, engage citizens, and accelerate employment and economic growth opportunities to control corruption in Nepal.